Postnatal depression among Sudanese women: prevalence and validation of the Edinburgh Postnatal Depression Scale at 3 months postpartum - Khalifa DS; Glavin K; Bjertness E; Lien L (Dove Medical Press, 2015)
Dina Sami Khalifa,1,2 Kari Glavin,3 Espen Bjertness,1 Lars Lien4,51Department of Community Medicine, Institute of Health and Society, Faculty of Medicine, University of Oslo, Norway; 2Faculty of Health Sciences, Ahfad University for Women, Omdurman, Sudan; 3Diakonova University College, Oslo, 4National Advisory Board on Dual Diagnosis, Innlandet Hospital Trust, Hamar, 5Department of Public Health, Hedmark University College, Elverum, NorwayPurpose: Postnatal depression (PND) rates in low-resource countries have reached levels between 4.9% and 59%. Maternal mental health has not been researched in Sudan, and there are no existing statistics on prevalence or significant risk factors for PND. Consequently, no screening test has been validated to screen for PND at the primary health care level. This study investigates the 3 months prevalence of PND and validates the Edinburgh Postnatal Depression Scale (EPDS) against the Mini-International Neuropsychiatric Interview (MINI).Methodology: Pregnant Sudanese women in the second and third trimesters were recruited to the study during routine antenatal care visits in two major maternity hospitals in Khartoum state. They were screened for PND at 3 months postpartum using the EPDS. Test positive women were matched with test negative women according to nearest date of birth. A clinical psychologist verified their depression status using the MINI.Results: The follow-up rate was 79%. At a cutoff point of ≥12, the 3 months prevalence of PND was 9.2%. The sensitivity and specificity of the EPDS were 89% and 82%, respectively. The EPDS and MINI showed a strong positive relationship (odds ratio =36). The positive predictive value and negative predictive value, using this study’s prevalence, were 33% and 98.7%, respectively. The receiver operator characteristic analysis showed an area under the curve of 0.89. The cut-off point ≥12 was the most acceptable point as it had the lowest number needed to diagnose (1.4) and a false-positive rate of 18%.Conclusion: The EPDS is a valid tool for screening for PND on a Sudanese population. It was accepted, easily administered, and understood by postnatal women. Health care personnel, especially village midwives, should be trained on screening and referral of depressed women for clinical evaluation and management. Due to limited resources available in Sudan, shorter screening tests need to be validated in the future.Keywords: Edinburgh Postnatal Depression Scale, Sudan, Epidemiology, Sensitivity, specificity, developing countries